Epileptogenesis in Calcified Neurocysticercosis - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2012)
Researchers at Sanjay Gandhi Post Graduate Institute of Medical Sciences, Lucknow, India, and University of Texas Medical School at Houston performed dynamic contrast-enhanced (DCE) MRI and determined serum matrix metalloproteinase-9 (MMP-9) levels and MMP-9 gene polymorphisms in 30 subjects with a single calcified lesion of neurocysticercosis without any perilesional abnormality.